Sistematika Literatur Review: Program Teaching Factory Dalam Peningkatan Relevansi Lulusan Dengan Dunia Kerja - Lena Rusmiyati; Nurhattati Nurhattati; Kamaludin Kamaludin (Departement of Mathematics Education, 2025)
This research constitutes a Systematic Literature Review (SLR) aimed at evaluating the implementation of the Teaching Factory program in Vocational High Schools (SMK) to enhance the quality of graduates and its relevance to labor market needs. Data collection of articles was conducted using the Publish or Perish (PoP) application, followed by analysis through the PRISMA method. The focus of this study spans the period from 2020 to 2024, during which educational policies in Indonesia have emphasized strengthening workforce skills through vocational programs and the revitalization of SMK.The approach employed in this study is qualitative, utilizing secondary data analysis and surveys. The findings indicate that journal publications regarding the Teaching Factory during this period encompass various sectors, benefits, and implementations. However, research on the evaluation of the Teaching Factory program's implementation in enhancing graduates' relevance to the labor market remains relatively limited. The Teaching Factory learning model has proven effective in increasing student motivation and positively impacting the quality of SMK.